Small vessel disease: mechanisms and clinical implications. Issue 7 (July 2019) - Wardlaw, Joanna M; Smith, Colin; Dichgans, Martin
Summary: Small vessel disease is a disorder of cerebral microvessels that causes white matter hyperintensities and several other common abnormalities (eg, recent small subcortical infarcts and lacunes) seen on brain imaging. Despite being a common cause of stroke and vascular dementia, the underlying pathogenesis is poorly understood. Research in humans has identified several manifestations of cerebral microvessel endothelial dysfunction including blood–brain barrier dysfunction, impaired vasodilation, vessel stiffening, dysfunctional blood flow and interstitial fluid drainage, white matter rarefaction, ischaemia, inflammation, myelin damage, and secondary neurodegeneration. These brain abnormalities are more dynamic and widespread than previously thought. Relationships between lesions and symptoms are highly variable but poorly understood. Major challenges are the determination of which vascular dysfunctions are most important in pathogenesis, which abnormalities are reversible, and why lesion progression and symptomatology are so variable. This knowledge will help to identify potential targets for intervention and improve risk prediction for individuals with small vessel disease.